Analisis Perkembangan Kondisi Ekonomi Masyarakat Banjarmasin Tahun 1928 - Fathimah Dayaning Pertiwi; Amirullah, Ahmad; Moh Bahzar (History Education Department, Universitas Mulawarman, 2023)
News in Banjarmasin published in the Bintang Borneo Economic Newspaper focused on 1928 from March to May with the aim of knowing economic developments in the Banjarmasin area. This research uses a descriptive qualitative method with the approach used in analyzing namely using a historical analysis approach. Historical analysis is an analysis that refers to the aim of reconstructing events that occurred in the past objectively and systematically. The primary source for this research uses archives from newspapers or newspapers, while secondary sources are obtained from books, journals and websites which contain explanations about economic developments.